DECONSTITIONALIZE TO DEMOCRATIZE: ARMED FORCES AND POLICE IN THE NEW CONSTITUTION - Contreras, Pablo; Salazar Pizarro, Sebastián (Política. Revista de Ciencia Política, 2020)
This paper describes and critically analyzes the institutional design and the role of the Armed Forces and Order and Public Security Forces, established by the 1980 Constitution, in light of the constitutional process that Chile is experiencing. First, it analyzes the "Power of Security" and the normative autonomy recognized to them, verifying the elements that are maintained in the current Constitution. Second, based on a prospective review of six subjects related to the functions of the armed forces, the text concludes the need to remove from the Constitution a series of elements, with the aim of strengthening the democratic subordination of the military and police.